Development and Physico-Nutritional Evaluation of Sweet Potato Flour Based Gluten Free Cookies - GIRI, NAMRATA ANKUSH; Sheriff, J T; Sajeev, M S; C, Pradeepika (JOURNAL OF ROOT CROPS, 2016)
Sweet potato flour based gluten free cookies suitable for coeliac patient were developed using sweet potato flour (40-60%), rice flour (20-25%), sorghum flour (15-20%) and cassava flour (5-15%). Cookies were developed using creamery method and evaluated for physical properties, textural analysis, proximate composition and sensory characteristics. Spread ratio of sweet potato flour based gluten free cookies varied between 3.95 to 5.49 and it was decreased with increasing level of sweet potato flour. Breaking hardness of different cookies was increased with increasing level of sweet potato flour in flour blends. Minerals content in sweet potato flour based gluten free cookies was higher than maida based cookie. Gluten free cookies prepared with sweet potato flour showed the maximum crude fiber content as compared to maida based cookie. Results indicated that sweet potato flour based gluten free cookies for coeliac patient with overall sensory acceptable can be prepared using sweet potato flour 60% with rice flour 20%, sorghum flour 15% and cassava flour 05%.